STRESS MARKERS ON THE LUMBAR VERTEBRAE - Alifya Grahanata (Jurnal Biosains Pascasarjana, 2024)
Woven sarong craftsmen in Wedani Village in carrying out their work activities make sarongs using non- machine looms. Work starts from 07.00 to 16.30 for 6 working days a week by producing 1 to 4 sarongs per day. The craftsman's activities when moving the loom have a support load that lies on the lumbar vertebrae, because when weaving the craftsman is in a 90° sitting position. This study aims to describe the shape of stress markers and their location related to length of work, intensity of activity, and limb movement muscles of the upper and lower extremities which have the greatest influence on the appearance of osteophytes in the lumbar vertebrae. The research was conducted using data collection techniques in the form of X-ray results and supported by literature studies related to the muscular system in the lumbar vertebrae which affect the movement system. The results of X-ray analysis showed that there were 42.8% stress markers in the form of osteophytes in the lumbar vertebrae of woven sarong craftsmen with the same location of osteophytes. Stress markers appear in the form of osteophytes on the lumbar vertebrae of woven sarong craftsmen according to the height of the age factor, namely 43-47 years, length of working period, namely 30-35 years, intensity of work, and the burden on the limbs, namely the upper extremities and lower extremities on the lumbar vertebrae as a support when moving the loom. Based on the X-ray results of the lumbar vertebrae of the woven sarong craftsmen in Wedani Village, it shows that out of 7 samples, 3 samples experienced stress markers in the form of osteophytes on the lumbar vertebrae and 4 samples had normal conditions.